Analisis Aspek Legalitas Pada Produksi Meubel UD. Aji Jati Di Kecamatan Kasiman Bojonegoro - Anisa Lestari; Abdur Rohman (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Currently, the tourism industry in Indonesia has increased from time to time since the number of Covid-19 pandemic outbreaks decreased. The development of the tourism industry is certainly directly proportional to other sectors such as the trade sector. However, the current trade industry with all the easy opportunities makes people competing to set up a business but without being very unfortunate because it is not balanced with compliance with the law. Many businesses ignore the legal aspects of business licensing, raising doubts about the legality of their business. Usually this happens to umkm in Indonesia. This study aims to determine the business feasibility that will be tested in the furniture production business in the Bojonegoro area to see the feasibility of its business when viewed in terms of company legality in its legal aspects. The method used in this study is qualitative descriptive with primary data type. Data collection techniques in this study are by observation and direct interviews with the parties concerned to collect actual information. The results of the research are known that UD's furniture production business. Aji Jati can be said to be a viable business because it has met the requirements and rules related to the legality of the company in terms of legal aspects. The legal aspect is indeed the main aspect that must be fulfilled before establishing a business.